A RARE CASE OF SPONTANEOUS PNEUMOCEPHALUS AS A COMPLICATION OF NONTRAUMATIC CEREBROSPINAL FLUID RHINORRHEA. AN EVIDENCEBASED REVIEW - E. V. Shelesko; O. S. Zaitsev; N. A. Chernikova (Архивъ внутренней медицины, 2017)
Pneumocephalus is defined as intracranial air. Pneumaticcephaly is associated with several etiological factors, such as head injuries, surgical interventions, infections and neoplasms. On average, the incidence of posttraumatic pneumocephaly fluctuates between 0.5-1% of all skull injuries. Spontaneous pneumocephalus without cerebrospinal fluid leak is very rare. Clinical manifestations of pneumocephaly depend on the location and volume of air in the cranial cavity. The most common and described symptoms are headache, “splashing sound”, rhinorrhea and otorrhea, meningism, dysfunction of cerebrospinal nerves, epileptic seizures, collaptoid states, psychiatric symptoms. In this article we report an effective treatment of spontaneous cerebrospinal fluid leak, complicated by pneumocephaly and meningitis. A 57-year-old patient was admitted to National Scientific and Practical Center of Neurosurgery named after academician N.N. Burdenko in the department of neurotrauma in a serious condition. Medical history: One year ago the patient began to notice the flow of clear fluid from the left nasal passage, which periodically spontaneously ceased, then again recurred. Two months before admission she noticed headaches, fever, nausea, vomiting. Objective data on admission: serious condition, level of consciousness: stunning, drowsiness, lethargy. There is stiff neck. The SCT of the brain shows destructive changes in the posterior wall of the main sinus, with the presence of the exudative component in the left parts of the main sinus, the latticed labyrinth, the posterior parts of the left maxillary sinus. In the ventricular system, basal cisterns, anterior sections of the frontal lobes, the accumulation of air is determined. Under general anesthesia, the operation “Endoscopic endonasal plastic of a complex skull base defect in the region of the sphenoid sinus on the left under the control of the navigation system” was performed. There was subdural injection of 1.0 ml of 5% of Fluorescein sodium. CSF rhinorrhea stopped completely after the surgery with complete resolution of pneumocephalus before discharge.